Environmental Awareness and Attitudes of University Students: The Case of Türkiye - ACIBUCA, Veysi; KAYA, Aybüke (ISPEC Tarım Bilimleri Dergisi, 2024)
In recent years, environmental problems have been a major concern all over the world and are a threat to the quality of life of societies. Considering that most environmental problems are caused by people’s lifestyles, values and attitudes, an understanding of education that changes the way today’s people view nature and shapes their values and attitudes is essential to preventing environmental problems. Conducting studies to increase the level of awareness and consciousness of individuals about the environment is one of the main ways to eliminate these problems and ensure environmental sustainability. This study was conducted in Türkiye to measure the environmental awareness and knowledge of university students living in various provinces. In this study, 403 university students living in different provinces in Türkiye were interviewed. According to the results, it was found that the average age of the individuals was 22 years and about three-fourths of them had knowledge about environmental problems, but they thought that the given information about the environment was insufficient. According to these findings, people generally have environmental awareness and ideas about consumption and natural resources. However, it was found that there was a high demand for participation in environmental training at universities. Students emphasized that the most important source of information on environmental issues was the internet. In addition, a significant number of students believed that environmental training at universities should be part of the curriculum. It is believed that training provided to young people will raise the awareness of individuals and be effective for their families and friends. Environmental education is central to raising environmental awareness in individuals and raising awareness about environmental protection. It is thought that education given to individuals as a group will have an easier effect on behavior change. Gathering individuals from different provinces under one roof at universities will facilitate intercultural interaction and pave the way for environmental sustainability. Changes in the behavior of individuals will have a significant impact on future generations. Therefore, it is hoped that the results obtained in this study will contribute to environmental and climate change policies.